NPS in Poland: Problems and Solutions - K. Tkaczyk-Rymanowska (Emerging Trends in Drugs, Addictions, and Health)
Introduction: According to a polish law, NPS is a natural or synthetic substance acting on the central nervous system, other than a psychotropic substance or a narcotic drug, posing health or social risks comparable to the risks posed by them, or which mimic the effects of these substances. Whoever possesses NPS, is subject to a fine. If there is a significant amount of NPS, the perpetrator is subject to a fine, the penalty of restriction of liberty or the penalty of deprivation of liberty for up to 3 years. If there is a NPS in insignificant amounts, intended for personal use, the proceedings may be discontinued, if the ruling against the perpetrator would be ineffective due to the circumstances. NPS use is very widespread in Poland, specially some of their types. Purpose: NPS use as a phenomenon: Multidimensional - as to the factors necessary for its occurrence (drug-emotions-repeatability), Multifactorial - as to the sources (social impact of specific groups, the scale of supply, social status, cultural factors, life perspectives). Scope: NPS use as a problem: Social - a manifestation of social pathology Medical - addiction as a disease entity Legal - criminal liability for the crime of NPS possession. Social problems: Loss of the ability to live in a family, in society, to perform professional duties, Disappearance of social relations, Codependency, Development of other social pathologies (e.g., prostitution), Stigmatization of NPS addicts in society, marginalization and rejection consumer in social contacts, The problem of the so-called recreational use. Medical problems: Gradual destruction of health, sometimes up to the complete degradation of the person, the development of other diseases, including mental disorders, the phenomenon of tolerance, Politoxicomania, Risky behavior, loss of control over the behawior, Addiction treatment costs, the need to expand NPS treatment facilities (and methods), Difficulties in treating people after taking NPS (unknown ingredients). Legal problems: Development of drug-related crime and other forms of crime (e.g. theft, robbery), Criminalization, stigmatization of perpetrators, preventing them from returning to life in society (e.g. recording a conviction in the National Criminal Register makes it difficult to navigate the labor market), Legislative problems, constitutional doubts what really means “NPS”. Solving problems related to NPS addiction: Development of harm reduction system Addiction treatment centers Therapies/psychotherapies Prevention (e.g. phone apps) Supervision and control over NPS Criminalizing NPS possession (good idea?).